Efektivitas Sertifikat P-IRT dalam Meningkatkan Kepercayaan Konsumen pada Produk UMKM di Martajasah untuk Memperluas Peredaran Pasar - Hikmatus Sakinah; Ruski (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
The business world is now starting to compete globally to gain customer satisfaction. Seeing the current developments, Micro, Small and Medium Enterprises (MSMEs) are a form of productive business owned by individuals or business entities engaged in the scope of trading activities that have different characteristics. This study aims to analyze the effectiveness of the Household Industry Food Certificate (P-IRT) in increasing consumer confidence and its role in expanding market circulation. The methodology used is a qualitative descriptive approach with data collection techniques through interviews, observations, and documentation of MSME actors and local consumers. In conclusion, the P-IRT Certificate is said to be effective in increasing the competitiveness of MSME products in local and regional markets. However, the uniqueness of taste is also a consideration for consumers to buy products besides paying attention to products labeled P-IRT.